Stakeholder perspectives from 15 countries in Africa on barriers in snakebite envenoming research and the potential role of research hubs. - Ymkje Stienstra; Leslie Mawuli Aglanu; Janna M Schurer; Rhona Mijumbi; Jean Bosco Mbonigaba; Abdulrazaq G Habib; Brent Thomas; Jonathan Steinhorst; Rachael Thomson; Sara Padidar; John H Amuasi; George O Oluoch; et al. (PLoS Neglected Tropical Diseases, 2023)
Snakebite envenoming is a debilitating neglected tropical disease disproportionately affecting the rural poor in low and middle-income countries in the tropics and sub-tropics. Critical questions and gaps in public health and policy need to be addressed if major progress is to be made towards reducing the negative impact of snakebite, particularly in the World Health Organisation (WHO) Africa region. We engaged key stakeholders to identify barriers to evidence-based snakebite decision making and to explore how development of research and policy hubs could help to overcome these barriers. We conducted an electronic survey among 73 stakeholders from ministries of health, health facilities, academia and non-governmental organizations from 15 countries in the WHO Africa region. The primary barriers to snakebite research and subsequent policy translation were limited funds, lack of relevant data, and lack of interest from policy makers. Adequate funding commitment, strong political will, building expert networks and a demand for scientific evidence were all considered potential factors that could facilitate snakebite research. Participants rated availability of antivenoms, research skills training and disease surveillance as key research priorities. All participants indicated interest in the development of research and policy hubs and 78% indicated their organization would be willing to actively participate. In conclusion, our survey affirms that relevant stakeholders in the field of snakebite perceive research and policy hubs as a promising development, which could help overcome the barriers to pursuing the WHO goals and targets for reducing the burden of snakebite.